Government financial support for productivity output in agriculture sector - Toshqulov, Abduqodir (International Journal of Psychosocial Rehabilitation, 2020)
The rapidly growing agricultural infrastructure in regions has changed way of improvement via labor, capital, and land. Influence of financial capital moves as a potential locomotive for agricultural productivity. Thus, it is important to study the feasibility of inputs as a financial support by government in competitive economic growth. This paper estimated the degree of principles of government financing way of best output in agriculture sector in regions. Main purpose can be discussed in ways of methodological aspects and fundamental approaches of financing. As for the results author suggests decomposition structure of financing and borrowing classification of money. Conclusion can be drawn by summarizing up all fundamental approach of financing instruments, structure and comparative analyses of agriculture development for increasing effective growth.